For \( \mathrm{f}(\mathrm{x})=\mathrm{x}^{2}+2 \) and \( \mathrm{g}(\mathrm{x})=\sqrt{4-\mathrm{x}} \), find a. \( (\mathrm{f} \circ \mathrm{g})(\mathrm{x}) \); b. the domain of \( \mathrm{f} \circ \mathrm{g} \) a. \( (\mathrm{f} \circ \mathrm{g})(\mathrm{x})=\square \) (Simplify your answer.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To find \( (\mathrm{f} \circ \mathrm{g})(\mathrm{x}) \), we need to substitute \( g(x) \) into \( f(x) \). 1. Start with \( g(x) = \sqrt{4 - x} \). 2. Now substitute \( g(x) \) into \( f(x) \): \[ (\mathrm{f} \circ \mathrm{g})(\mathrm{x}) = f(g(x)) = f(\sqrt{4 - x}) = (\sqrt{4 - x})^2 + 2 \] 3. Simplifying that gives: \[ (\sqrt{4 - x})^2 = 4 - x \] Thus, \[ f(g(x)) = (4 - x) + 2 = 6 - x \] So, \( (\mathrm{f} \circ \mathrm{g})(\mathrm{x}) = 6 - \mathrm{x} \). Now, for the domain of \( f \circ g \): To find the domain, we need to consider the domain of \( g(x) \) and the values that \( g(x) \) can take. 1. The function \( g(x) \) is defined when \( 4 - x \geq 0 \), which means \( x \leq 4 \). 2. Moreover, \( g(x) = \sqrt{4 - x} \geq 0\), meaning \( \sqrt{4 - x} \) can take any value from \( 0 \) to \( 2 \) (as plugging in \( 0 \) and \( 4 \) results in \( g(x) = 0 \) and \( g(x) = 2 \), respectively). Thus, the output of \( g(x) \) lies in the interval \([0, 2]\), where \( f(x) \) has no restrictions. Therefore, the domain of \( f \circ g \) is all \( x \) values such that \( x \leq 4 \). Thus: Domain of \( (\mathrm{f} \circ \mathrm{g}) \) is \( (-\infty, 4] \).